Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian di Kalangan Mahasiswa Manajemen UNIMED (Studi Kasus : Fore Coffee) - Olivia Sembiring; Azri Nuansa Indah Nasution; Nadia Natalia Sinurat; Azra Lena Nuraina; Nicko Fernando Rajagukguk; Nurul Wardani (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study was conducted to analyze the influence of price and product quality on purchasing decisions among Management students at Medan State University with a case study on Fore Coffee. This study used a quantitative approach with a survey method using a Google Form-based questionnaire. The research sample consisted of 60 respondents randomly selected from the student population who had purchased Fore Coffee products in the last three months. Data were analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, and F-test tests using IBM SPSS Statistics 27. The results of the analysis assessed that the price variable had a significant effect on purchasing decisions with a significance value of 0.030 (<0.05), while product quality had no significant effect with a significance value of 0.948 (>0.05). Simultaneously, price and product quality had a significant effect on purchasing decisions, which was indicated by an adjusted R square value of 0.44, which means that both independent variables explained 44% of the variation in purchasing decisions. Thus, the results show that the price factor is the most influential factor in students' purchasing decisions for Fore Coffee products differentiated by product quality